A new species of Supramontana Carbayo & Leal-Zanchet (Platyhelminthes, Continenticola, Geoplanidae) from the Interior Atlantic Forest - Negrete, Lisandro Hector Luis (2014)
Supramontana argentina sp. nov. (Platyhelminthes, Continenticola, Geoplanidae) from north-eastern Argentina is herein described. The new species differs from Supramontana irritata Carbayo & Leal-Zanchet, 2003 from Brazil, the only species of this genus so far described, by external and internal morphological characters. Supramontana argentina sp. nov. is characterized by having a colour pattern with a yellowish median band, thin para-median black stripes, and two dark grey lateral bands on the dorsal surface. The most outstanding features of the internal morphology are a ventral cephalic retractor muscle almost circular in cross section, prostatic vesicle extrabulbar, tubular and very long, and penis papilla conical and blunt with a sinuous ejaculatory duct.